2022
DOI: 10.1002/uog.24936
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of transvaginal ultrasound for detection of endometriosis using International Deep Endometriosis Analysis (IDEA) approach: prospective international pilot study

Abstract: Objective To evaluate the diagnostic accuracy of transvaginal ultrasound (TVS) in predicting deep endometriosis (DE) following the International Deep Endometriosis Analysis (IDEA) consensus methodology. Methods This was an international multicenter prospective diagnostic accuracy study involving eight centers across six countries (August 2018-November 2019). Consecutive participants with endometriosis suspected based on clinical symptoms or historical diagnosis of endometriosis were included. The index test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
(39 reference statements)
2
24
0
Order By: Relevance
“…Regarding the DIE of the bladder, uterosacral ligaments, vagina, rectovaginal septum, RVS, and overall pelvis, TVS had a marginally higher specificity but lower sensitivity than MRI. The second study by Leonardi et al was an international multicentre prospective study reporting on the performance of TVS only [ 28 ]: they found a higher TVS detection rate of DE overall than that reported by the most recent Cochrane meta-analysis (sensitivity, 79% [ 6 ]), but lower specificity (specificity, 94% [ 6 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the DIE of the bladder, uterosacral ligaments, vagina, rectovaginal septum, RVS, and overall pelvis, TVS had a marginally higher specificity but lower sensitivity than MRI. The second study by Leonardi et al was an international multicentre prospective study reporting on the performance of TVS only [ 28 ]: they found a higher TVS detection rate of DE overall than that reported by the most recent Cochrane meta-analysis (sensitivity, 79% [ 6 ]), but lower specificity (specificity, 94% [ 6 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the ENDO Study enrolled 131 women from the general population who had not presented for gynecologic evaluation, among whom magnetic resonance imaging was used to diagnose endometriosis in 11% 123. Although the sensitivity of transvaginal ultrasonography is maximized only for endometriomas, technological and training advances are improving detection of all sub-phenotypes of endometriotic lesions 124125. Saline infusion sonoPODography is a novel technique that may be able to diagnose superficial peritoneal endometriosis on ultrasonography, although it needs to be validated 126…”
Section: Diagnosis and Monitoringmentioning
confidence: 99%
“…TVUS is also reliable at measuring the lesion-to-anal-verge distance of rectosigmoid DE, thereby estimating the height of the bowel anastomosis in patients undergoing a-full-thickness resection either by discoid resections or segmental resections [ 30 , 31 ]. A recent prospective study performed by the IDEA group found a higher TVUS detection rate of DE overall than that reported by the most recent meta-analysis on the topic (sensitivity of 79%), but with a lower specificity [ 32 ].…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%
“…The indirect signs are the following: retractile periureteral adhesions (visible as low-signal-intensity lines with angular deviation) or ureteral dilatation cranial to the obstruction site [ 74 ]. A more infrequent occurrence is hydronephrosis, which is easily detectable with T2W (sensitive to the water) or with the more advanced T2W sequences and delayed contrast-enhanced 3D with higher spatial resolution [ 32 ] and magnetic resonance urography. For the detection of endometriosis in the ureter, Sillou et al [ 75 ] demonstrated that MRI is more sensitive than surgery (91% vs. 82%) but less specific (59% vs. 67%)…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation